Parents' and clinicians' views of an interactive booklet about respiratory tract infections in children: a qualitative process evaluation of the EQUIP randomised controlled trial. - Francis, N; Phillips, R; Wood, F; Hood, K; Simpson, S; Butler, C (BioMed Central, 2013)
BACKGROUND: 'When should I worry?' is an interactive booklet for parents of children presenting with respiratory tract infections (RTIs) in primary care and associated training for clinicians. A randomised controlled trial (the EQUIP study) demonstrated that this intervention reduced antibiotic prescribing and future consulting intentions. The aims of this qualitative process evaluation were to understand how acceptable the intervention was to clinicians and parents, how it was implemented, the mechanisms for any observed effects, and contextual factors that could have influenced its effects. METHODS: Semi-structured interviews were conducted with 20 parents and 13 clinicians who participated in the trial. Interviews were audio-recorded and transcribed verbatim. Data were analysed using a framework approach, which involved five stages; familiarisation, development of a thematic framework, indexing, charting, and interpretation. RESULTS: Most parents and clinicians reported that the 'When should I worry' interactive booklet (and online training for clinicians) was easy to use and valuable. Information on recognising signs of serious illness and the usual duration of illness were most valued. The interactive use of the booklet during consultations was considered to be important, but this did not always happen. Clinicians reported lack of time, lack of familiarity with using the booklet, and difficulty in modifying their treatment plan/style of consultation as barriers to use. Increased knowledge and confidence amongst clinicians and patients were seen as key components that contributed to the reductions in antibiotic prescribing and intention to consult seen in the trial. This was particularly pertinent in a context where decisions about the safe and appropriate management of childhood RTIs were viewed as complex and parents reported frequently receiving inconsistent messages. CONCLUSIONS: The 'When should I worry' booklet, which is effective in reducing antibiotic prescribing, has high acceptability for clinicians and parents, helps address gaps in knowledge, increases confidence, and provides a consistent message. However, it is not always implemented as intended. Plans for wider implementation of the intervention in health care settings would need to address clinician-related barriers to implementation. TRIAL REGISTRATION: ISRCTN46104365.